Ingestion of plastic by fish: A comparison of Thames Estuary and Firth of Clyde populations. (December 2018) - McGoran, Alexandra R.; Cowie, Phillip R.; Clark, Paul F.; McEvoy, James P.; Morritt, David
Abstract: This study compared plastic ingestion between pelagic and benthic fish populations from two UK watersheds: the Thames Estuary and the Firth of Clyde. The alimentary canals of 876 individuals were examined. Of twenty-one estuarine species investigated, fourteen ingested plastics, including predator (fish) and prey (shrimp) species. Overall, 32% of organisms ingested plastic, mostly fibres (88% of total plastics). More flatfish (38%) ingested plastics than other benthic species (17%). In the Thames, more plastic was ingested by pelagic species (average number of plastic pieces ingested: 3.2) and flatfish (average number of plastic pieces ingested: 2.9) than by shrimp (average number of plastic pieces ingested: 1). More fish from the Clyde ingested plastic than similar Thames species (39% compared to 28% respectively); however, the average amount of plastic ingested did not differ between the sites. Graphical abstract: Highlights: Microfibres were the most recovered plastic. Microplastic is ingested by both pelagic and benthic fish and brown shrimp. 14 fish species from the Clyde and Thames estuaries ingested plastic. 32% of organisms in this study ingested plastic. Polyester was the most commonly ingested plastic.